Transforming Public Procurement: The Organizational Change Model of UKPBJ Central Buton - Abidin, Zainul; Parasit, La; Asmiddin, Asmiddin; Islamy , La Ode Syaiful; Syarif , LM (Jurnal Administrasi Publik (Public Administration Journal), 2025)
This article aims to analyze the organizational transformation of the goods and services procurement unit in Central Buton Regency using Kurt Lewin’s change theory and change management perspectives. This research employed a qualitative descriptive approach, collecting data through interviews, observation, and document analysis. Data were analyzed qualitatively through preparation, organization, reduction, and presentation. The transformation occurred in three stages: unfreezing through the socialization of changes in structure, human resources, risk, technology, and budget, change with the formation of a centralized, performance-driven structure, and refreezing through capacity building, functional staffing, technology enhancement, and budget adjustment. The resulting model integrates Lewin's framework with transformational leadership, competent teams, human resources development, and technological innovation.